2013
DOI: 10.1063/1.4793629
|View full text |Cite
|
Sign up to set email alerts
|

Bond energy decomposition analysis for subsystem density functional theory

Abstract: We employed an explicit expression for the dispersion (D) energy in conjunction with Kohn-Sham (KS) density functional theory and frozen-density embedding (FDE) to calculate interaction energies between DNA base pairs and a selected set of amino acid pairs in the hydrophobic core of a small protein Rubredoxin. We use this data to assess the accuracy of an FDE-D approach for the calculation of intermolecular interactions. To better analyze the calculated interaction energies we furthermore propose a new energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 104 publications
0
25
0
Order By: Relevance
“…A recent energy decomposition analysis of subsystem DFT calculations [44] has shown that the inclusion of empirical van der Waals terms in the interaction energy has the effect of improving the binding energies calculated with GGA functionals. In line with those findings, we show that the FDE binding energies are dramatically improved if the non-additive correlation energy functional is made non-local in character and is evaluated with the Fluctuation-Dissipation Theorem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent energy decomposition analysis of subsystem DFT calculations [44] has shown that the inclusion of empirical van der Waals terms in the interaction energy has the effect of improving the binding energies calculated with GGA functionals. In line with those findings, we show that the FDE binding energies are dramatically improved if the non-additive correlation energy functional is made non-local in character and is evaluated with the Fluctuation-Dissipation Theorem.…”
Section: Discussionmentioning
confidence: 99%
“…First, Visscher and coworkers [44], demonstrated that the FDE coupled with semiempirical dispersion corrections yields accurate interaction energies. Second, Cha lasiński and coworkers [45], used a projector-based partitioning of HF and KS-DFT wavefunctions into fragment wavefunctions to define an interfragment dispersion correction calculated with the GCP formula which yielded excellent interaction energies.…”
Section: Introductionmentioning
confidence: 99%
“…But we do note the great promise of density embedding methods, of which there are various flavors. [47][48][49][50][51][52][53] However, we will not cover embedding methods further in this perspective, except to note that density embedding not only can serve as a way to speed up DFT calculations, but also it can serve as a new way to combine WFT with DFT, which is an approach that has great promise but is not fully covered in this article.…”
Section: B What Is Kohn-sham Dft?mentioning
confidence: 99%
“…This led to as accurate binding energies of weakly bonded molecular dyads as supersystem RPA [e.g., mean unsigned errors of < 0.5 kcal/mol against CCSD(T) on the S22 set [57,58] ]. Beyhan [59] also proposed a Grimme-like long-range correction to the nonadditive correlation energy which led to much improved interaction energies. To account for dispersion interactions between subsystems, eQE can include London dispersion forces as implemented in the main QE code base.…”
Section: Periodic Systemsmentioning
confidence: 99%